Green Affinity : Evaluating the Perceptions of Youth on Climate Change and Renewable Energy - Ragu Prasadh, R.; Suresh, Jayshree (Prabandhan: Indian Journal of Management, 2016)
Climate change is one of the most critical global challenges of our times. With the drastic consequences visible worldwide, it is the need of the hour to combat this crisis and a large scale adoption of renewable energy is one of the promising solutions. In this fight against climate change, the youth play a vital role since they are the next generation and inherit the responsibility to build a sustainable future. Research in the area of youth and specifically students' conceptions regarding geo-science phenomena is lacking in India. Hence, the present study aimed to examine the students' awareness about climate change and renewable energy. It also intended to analyze the key factors that influence their intention to use renewable energy. The study sample consisted of 124 students from SRM University in Kancheepuram District, Tamil Nadu. The research findings showed that a majority of the respondents were aware of climate change and renewable energy technology; but it was superficial. However, 30% of the respondents were willing to use renewable energy in the future. The results revealed that awareness, perception of usefulness and ease of using technology, and behavioural control were important factors affecting respondents' intention to adopt renewable energy. Based on these findings, we make certain recommendations to foster knowledge and enthusiasm among the younger generation to make them more participative in the fight against climate change.